Antistatic adhesive tape for backgrinding
Patent Information
- Application Number
- JP2025059693
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166630000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to an antistatic adhesive tape for backgrinding. [Background technology]
[0002] In the semiconductor wafer processing process, after forming a pattern on the surface of the semiconductor wafer, a so-called backgrinding process is performed in which the back surface of the semiconductor wafer is ground to a predetermined thickness. In this backgrinding process, backgrinding tape (surface protection tape) is applied to the surface (pattern side) of the semiconductor wafer to protect the pattern.
[0003] In semiconductor wafer processing using backgrinding tape, static electricity is generated due to bonding / peeling, triboelectric charging, and spray charging. For example, static electricity is generated on semiconductor elements when bonding or peeling backgrinding tape, and during back grinding in the backgrinding process. Static electricity is also generated when the backgrinding tape is transported on a roll. This static electricity can cause problems such as damaging circuits formed on the semiconductor wafer (electrostatic discharge damage to electronic components) or making it easier for foreign matter such as dust to adhere to the circuits.
[0004] As a countermeasure against static electricity generated during the processing of semiconductor wafers as described above, a technology for imparting antistatic properties to backgrinding tape is known. For example, this can be achieved by kneading an antistatic agent into the resin that makes up the base film of the backgrinding tape, by incorporating an antistatic agent into the adhesive layer, or by providing a coating layer containing an antistatic agent (also referred to as an "antistatic coating layer") on the outermost surface of the base film or the outermost surface of the adhesive layer. For example, Patent Document 1 describes an adhesive sheet comprising a base layer and an adhesive layer provided on one side of the base layer, wherein in a peel test at a peeling speed of 300 mm / min, the peeling band voltage generated when the adhesive sheet is peeled from the release film is 500V or less. An example in Patent Document 1 describes an adhesive sheet that achieves the above-mentioned peeling band voltage from the release film, which contains at least an antistatic agent in the adhesive layer. Furthermore, Patent Document 2 describes an adhesive sheet for fixing electronic components having a base film and an adhesive layer, wherein an outer antistatic layer and an outer protective layer are provided in that order on the side of the base film opposite to the side on which the adhesive layer is formed. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2023-133232 [Patent Document 2] International Publication No. 2021 / 117398 [Overview of the project] [Problems that the invention aims to solve]
[0006] With technological advancements, semiconductor wafer processing tends to generate more static electricity. For example, the widespread adoption of flip-chip mounting methods has increased the need for higher density bumps and narrower wiring pitches on the wafer surface, making semiconductor wafers more susceptible to static electricity than ever before. Furthermore, the increased speed of backgrinding tape peeling also contributes to increased static electricity generation. Therefore, backgrinding tapes require further improvements in their antistatic properties.
[0007] In addition to the improvement in antistatic performance mentioned above, our research has revealed that the following problems are prone to occur in the backgrinding process. In the backgrinding process, the wafer is usually cooled with water while being ground to thin the wafer to a predetermined thickness, but a considerable amount of the antistatic component contained in the tape dissolves or desorbs into the water. This dissolution or desorption can cause contamination of the wafer circuit and degrade semiconductor quality. Furthermore, it can lead to corrosion of the backgrinding equipment, resulting in problems such as increased maintenance frequency and shortened equipment lifespan.
[0008] The present invention aims to provide an antistatic adhesive tape for backgrinding that possesses desirable excellent antistatic properties and can sufficiently suppress the elution or detachment of antistatic components into water during the backgrinding process (excellent water resistance). [Means for solving the problem]
[0009] The above-mentioned problems of the present invention were solved by the following means. <1> An antistatic adhesive tape for backgrinding comprising an antistatic coating layer, a base film, and an adhesive layer in this order, The antistatic coating layer contains carbon nanotubes as an antistatic agent, If, before the following process (A), the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R1, and after the following process (A), the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R2, Antistatic adhesive tape for backgrinding that satisfies the following conditions (1) and (2). (1) The surface resistivity R1 is 1.0 × 10 5 ~1.0×10 12 It is Ω / sq. (2) The surface resistivity change rate Z calculated by the following formula (Equation I) is between 1.0 and 20.0. (Formula I) Surface resistivity change rate Z = Surface resistivity R2 / Surface resistivity R1 <Treatment (A)> A sample of the antistatic pressure-sensitive adhesive tape for back grinding (100 mm long × 100 mm wide) is immersed in pure water at a temperature of 23°C for 24 hours, then taken out, gently rinsed with pure water to remove moisture, dried at 23°C, and then left to stand for 12 hours in an atmosphere at a temperature of 23°C and a relative humidity of 50%. <2> The antistatic pressure-sensitive adhesive tape for back grinding according to <1>, wherein the pH measured by the following water resistance test (B) is in the range of 6 to 8. <Water Resistance Test (B)> The pH of the immersion liquid obtained after immersing the sample of the antistatic pressure-sensitive adhesive tape for back grinding (100 mm long × 100 mm wide) in 10 ml of pure water at a temperature of 23°C for 24 hours is measured using pH test paper. <3> The antistatic pressure-sensitive adhesive tape for back grinding according to <1> or <2>, wherein the thickness of the antistatic coat layer is 10 to 90 nm. <4> The antistatic pressure-sensitive adhesive tape for back grinding according to any one of <1> to <3>, wherein the base film contains a polyester resin.
Effects of the Invention
[0010] The antistatic pressure-sensitive adhesive tape for back grinding of the present invention has a desired level of antistatic property and is excellent in water resistance.
Brief Description of the Drawings
[0011] [Figure 1] Figure 1 is a schematic cross-sectional view schematically showing one embodiment of the antistatic pressure-sensitive adhesive tape for back grinding of the present invention. Note that hatching indicating cross sections is omitted in Figure 1.
Modes for Carrying Out the Invention
[0012] In this invention, the surface of a semiconductor wafer refers to the surface of the semiconductor wafer that has irregularities, that is, the surface on which an integrated circuit (circuit pattern) is formed. The surface opposite to this surface is referred to as the back surface. In this invention, a numerical range represented using "~" means a range that includes the numbers written before and after "~" as the lower limit and upper limit, respectively. In this invention, "(meth)acrylic" is used to mean that it includes either "acrylic" or "methacrylic" or both.
[0013] [Anti-static adhesive tape for backgrinding] The antistatic adhesive tape for backgrinding of the present invention (hereinafter also simply referred to as "the tape of the present invention") comprises an antistatic coating layer, a base film, and an adhesive layer in this order. The antistatic coating layer contains carbon nanotubes as an antistatic agent. The tape of the present invention satisfies the following conditions (1) and (2) when, before the following treatment (A), the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R1, and after the following treatment (A), the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R2. (1) The surface resistivity R1 is 1.0 × 10 5 ~1.0×10 12 It is Ω / sq. (2) The surface resistivity change rate Z calculated by the following formula (Equation I) is between 1.0 and 20.0. (Equation I) Surface resistivity change rate Z = Surface resistivity R² / Surface resistivity R¹ <Process (A)> A sample of the antistatic adhesive tape for backgrinding (100 mm x 100 mm) is immersed in pure water at 23°C for 24 hours, then removed, lightly rinsed with pure water, drained, dried at 23°C, and left to stand for 12 hours in an atmosphere of 23°C and 50% relative humidity. The surface resistivities R1 and R2 are both values measured from the antistatic coat layer side (the side opposite to the pressure-sensitive adhesive layer) in an atmosphere at a temperature of 23°C and a relative humidity of 50%, and more specifically, are values measured by the methods described in the Examples below. When the pressure-sensitive adhesive layer of the tape of the present invention is of a radiation-curable type, the measurement of surface resistivity shall be performed before curing by radiation. In the above treatment (A), pure water means water having an electric conductivity of 1 μS / cm or less at 25°C.
[0014] The tape of the present invention can be suitably used as a back grind tape to be bonded to the uneven surface of a wafer when performing back grinding while pouring water onto the wafer. By satisfying the above (1), the tape of the present invention can exhibit sufficient antistatic properties in tapes used particularly when handling precision components sensitive to static electricity, such as during conveyance of the tape, during back grinding, during the dicing step, and other steps requiring temporary protection. Furthermore, in steps using an antistatic chuck for fixing the wafer, steps using laser, and the like, electricity hardly flows, so that defects in the wafer processing process are less likely to occur. In addition, by satisfying the above (2), sufficient water resistance is exhibited to reduce elution or detachment of the antistatic component in the back grinding step, and contamination of the wafer and / or contamination of the apparatus caused by the pressure-sensitive adhesive tape can be reduced. In addition, variation in antistatic properties before and after the back grinding step is reduced, and the antistatic performance can be maintained.
[0015] The surface resistivity R1 is preferably 1.0×10 6 ~1.0×10 12 Ω / sq., more preferably 1.0×10 7 ~1.0×10 12 Ω / sq., further preferably 1.0×10 7 ~1.0×10 11 Ω / sq.. The surface resistivity R2 is not particularly limited as long as the above (2) is satisfied together with the surface resistivity R1. The surface resistivity R2 is 1.0×10 5 ~2.0×10 13Ω / sq. is preferred, and 1.0 × 10 5 ~1.5×10 13 Ω / sq. is more preferred, 1.0 × 10 5 ~1.0×10 13 Ω / sq. is more preferable, and 1.0 × 10 6 ~1.0×10 13 Ω / sq. is more preferable, and 1.0 × 10 7 ~5.0×10 12 Ω / sq. is more preferable, and 1.0 × 10 7 ~1.0×10 12 Ω / sq. is more preferable, and 1.0 × 10 7 ~1.0×10 11 Ω / sq. is even more preferable. The surface resistivity R1 and R2 can be controlled by the amount of carbon nanotubes contained in the antistatic coating layer, the type of binder polymer constituting the antistatic coating layer, the thickness of the antistatic coating layer, and so on.
[0016] The surface resistivity change rate Z is more preferably 1.0 to 15.0, even more preferably 1.0 to 10.0, even more preferably 1.0 to 5.0, and even more preferably 1.0 to 3.0.
[0017] The surface resistivity R3 of the tape of the present invention, measured from the adhesive layer side before the above treatment (A), under an atmosphere of 23°C and 50% relative humidity, is not particularly limited. 6 ~1.0×10 12 Ω / sq. is preferred.
[0018] The tape of the present invention preferably has a pH in the range of 6 to 8, and more preferably in the range of 6 to 7, as measured by the following water resistance test (B). In the tape of the present invention, since carbon nanotubes are contained as an antistatic agent, the above pH is usually controlled within the above range. The above pH can also be controlled by the type of binder polymer that constitutes the antistatic coating layer. <Water resistance test (B)> A sample of antistatic adhesive tape for backgrinding (100mm x 100mm) is immersed in 10ml of pure water at 23°C for 24 hours, and the pH of the resulting immersion solution is measured using pH test paper.
[0019] The form of the tape of the present invention will now be described. Figure 1 shows one embodiment of a preferred layer configuration of the tape of the present invention. The tape 200 of the present invention comprises, in this order, an antistatic coating layer 10, a base film 20, and an adhesive layer 30. In the present invention, the laminate of the antistatic coating layer 10 and the base film 20 may be referred to as the base film 100 with an antistatic coating layer. The tape 200 of the present invention may or may not have, in addition to the antistatic coating layer 10, another antistatic coating layer 10b (not shown in Figure 1) between the base film 20 and the adhesive layer 30. Preferably, the tape of the present invention has only the antistatic coating layer 10 and not the antistatic coating layer 10b. In the tape 200 of the present invention, no other layers are typically laminated on the side of the antistatic coating layer 10, and the antistatic coating layer 10 is the outermost layer located on the side of the tape 200 of the present invention that is different from the adhesive layer 30. Furthermore, the tape 200 of the present invention may further include a release film (not shown in Figure 1) on the adhesive layer 30 for protecting the adhesive layer 30. The tape 200 of the present invention may be in the form of a laminated sheet having at least an antistatic coating layer 10, a base film 20, and an adhesive layer 30, or it may be in the form of this laminate wound into a roll. Here, in the present invention, "antistatic coating layer side" means the side of the antistatic coating layer 10 (opposite side from the adhesive layer 30) in the case of a layer configuration of antistatic coating layer 10 - base film 20 - adhesive layer 30. Even if the tape of the present invention has an additional antistatic coating layer 10b between the base film and the adhesive layer, the "antistatic coating layer side" is the side of the base film that has the antistatic coating layer 10 (the side opposite to the adhesive layer 30).
[0020] The components constituting the tape of the present invention will be described below.
[0021] (1) Base film 20 The resin constituting the base film 20 used in the tape 200 of the present invention (in this invention, "resin" includes elastomers and rubbers) is not particularly limited, and plastics, rubbers, etc., that are commonly used as materials constituting base films in the art to which the present invention belongs can be used. Examples of resins constituting the base film 20 include polyolefin resins consisting of homopolymers or copolymers of monomers containing ethylenically unsaturated groups, such as polyethylene such as low-density polyethylene, polypropylene, ethylene-propylene copolymer, polybutene-1, poly-4-methylpentene-1, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-acrylic acid copolymer, and ionomers; engineering plastics such as polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polycarbonate resins, polyurethane resins, and polymethyl methacrylate resins; synthetic rubbers such as styrene-ethylene-butene copolymers or styrene-ethylene-pentene copolymers; and thermoplastic elastomers such as polyamide-polyol copolymers. The resin constituting the base film 20 may be one of the above resins, or a combination of two or more. Furthermore, the base film 20 may be a single layer or a multi-layered film. In addition, the base film 20 may contain additives other than the resin mentioned above, such as colorants and antioxidants, as needed, to the extent that they do not affect the physical properties. The resin constituting the base film 20 preferably contains at least one of a polyolefin resin and a polyester resin, and more preferably contains a polyester resin. The proportion of polyester resin in the resin constituting the base film 20 may be, for example, 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more. The resin constituting the base film 20 may also be polyester resin. The same applies to the proportion of at least one type (or the total of two or more types) of polyolefin resin and polyester resin in the resin constituting the base film 20. In the above description concerning the proportion of polyester resin, "polyester resin" can be read as "at least one type (or the total of two or more types) of polyolefin resin and polyester resin."
[0022] The thickness of the base film 20 is preferably 30 to 120 μm, more preferably 40 to 100 μm, and even more preferably 40 to 90 μm. If the base film 20 is multi-layered, the "thickness of the base film 20" mentioned above refers to the sum of the thicknesses of all the layers that make up the base film 20.
[0023] (2) Antistatic coating layer 10 The antistatic coating layer 10 will be described below, but unless otherwise specified, matters other than its placement on the base film 20 can be applied to the antistatic coating layer 10b. The antistatic coating layer 10 contains carbon nanotubes as an antistatic agent. The antistatic coating layer 10 also typically contains a binder polymer.
[0024] (Carbon nanotubes) The carbon nanotubes mentioned above (hereinafter sometimes simply referred to as "CNTs") may be either single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs). MWCNT is constructed by stacking multiple cylindrical carbon walls of different diameters in a multilayered arrangement around a central axis, with the carbon walls forming a hexagonal network structure or a spiral pattern in multiple layers. Preferably, the MWCNT has 2 to 30 layers of carbon walls, and more preferably 2 to 15 layers. Furthermore, the carbon nanotubes may be dispersed individually in the antistatic coating layer 10, or they may be dispersed in bundles of multiple nanotubes.
[0025] Furthermore, when forming the antistatic coating layer 10, it is preferable to prepare an antistatic coating layer composition as described later and incorporate it as a dispersion liquid in which the CNTs are dispersed in a dispersion medium. When the dispersion medium is water or a mixture of water and an alcohol-based solvent, it is preferable to use a dispersant for dispersing the CNTs. There are no particular restrictions on the dispersant, and dispersants commonly used as dispersants for CNTs can be used. Examples include nonionic surfactants and anionic surfactants, with anionic surfactants such as alkylbenzene sulfonates (octylbenzene sulfonate, nonylbenzene sulfonate, dodecylbenzene sulfonate, etc.) being preferred. In addition, dispersants for CNTs manufactured by BYK that are not classified as binder polymers as described later (those that do not have film-forming properties and do not contribute to the development of adhesion with the base film 20) can also be used. The CNT dispersant described above is typically a component that remains in the antistatic coating layer 10. Furthermore, in the descriptions concerning the proportion of carbon nanotubes in the antistatic agent contained in the antistatic coating layer 10 described later, and in the descriptions concerning the content of the antistatic agent in the antistatic coating layer 10 described later, the carbon nanotube content shall be calculated including the CNT dispersant mentioned above.
[0026] (Binder polymer) The binder polymer included in the antistatic coating layer 10 is not particularly limited, as long as it can disperse the antistatic agent containing carbon nanotubes in the tape 200 of the present invention and reduce the elution or desorption of the antistatic agent containing carbon nanotubes. It can be any commonly used antistatic agent dispersant, binder polymer, etc., that has film-forming properties and can exhibit adhesion to the base film 20. The binder polymer preferably includes at least one of polyester resin, acrylic resin, and polyurethane resin, and more preferably acrylic resin. The proportion of at least one of polyester resin, acrylic resin, and polyurethane resin in the binder polymer (or the total proportion if there are two or more) may be, for example, 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more. The binder polymer in the antistatic coating layer may also be at least one of polyester resin, acrylic resin, and polyurethane resin.
[0027] Polyester resin refers to a resin in which the polymer constituting the polyester resin is composed of polyvalent carboxylic acid compounds and polyvalent hydroxy compounds. Examples of polycarboxylic acid compounds that can be used include terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 4,4'-diphenyldicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2-potassium sulfoterephthalic acid, 5-sodium sulfisoisophthalic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, glutaric acid, succinic acid, trimellitic acid, trimesic acid, pyromellitic acid, trimellitic anhydride, phthalic anhydride, p-hydroxybenzoic acid, monopotassium salt of trimellitic acid, and their ester-forming derivatives. Examples of polyvalent hydroxy compounds that can be used include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 2-methyl-1,5-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, p-xylylene glycol, bisphenol A-ethylene glycol adduct, bisphenol A-propylene glycol adduct, diethylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polytetramethylene oxide glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, sodium dimethylolethylsulfonate, and potassium dimethylolpropionate. Polyesters can be synthesized by selecting one or more of the above-mentioned polycarboxylic acid compounds and polyhydroxy compounds as appropriate, and carrying out a conventional polycondensation reaction. Furthermore, as part of the above-mentioned polycarboxylic acid compound, a polyester obtained by copolymerizing a compound having a sulfonic acid base or a compound having a carboxylic acid base to introduce sulfonic acid groups or carboxylic acid groups into the polyester skeleton, and then neutralizing and hydrophilizing it is also preferred. Examples of compounds having a sulfonic acid base include alkali metal salts of sulfonic acids or amine salts of sulfonic acids such as 5-sodium sulfisophthalic acid, 5-ammonium sulfisophthalic acid, 4-sodium sulfisophthalic acid, 4-methylammonium sulfisophthalic acid, 2-sodium sulfisophthalic acid, 5-potassium sulfisophthalic acid, 4-potassium sulfisophthalic acid, 2-potassium sulfisophthalic acid, and sodium sulfosuccinic acid. The amount copolymerized is usually 1 to 10 mol%, preferably 2 to 8 mol%, relative to the total polycarboxylic acid compound. The water dispersion stability can be further improved by introducing an appropriate amount of sulfonic acid groups.
[0028] Acrylic resin refers to a resin in which the polymer constituting the acrylic resin is a copolymer having (meth)acrylic acid ester as a constituent component (hereinafter referred to as "(meth)acrylic acid ester copolymer"). The content of (meth)acrylic acid ester constituent in the (meth)acrylic acid ester copolymer is 50 to 100% by mass, preferably 80 to 100% by mass. Preferred examples of the (meth)acrylic acid ester copolymer include a (meth)acrylic acid ester copolymer containing a constituent unit derived from at least two of the following: a (meth)acrylic acid ester monomer, a (meth)acrylic acid ester monomer having a functional group or polar group such as a hydroxyl group or a polyether structure (poly(alkylene oxy) structure), and (meth)acrylic acid. Examples of (meth)acrylic acid ester monomers include cycloalkyl (meth)acrylates and alkyl (meth)acrylates in which the alkyl group has 1 to 18 carbon atoms (preferably 1 to 12, more preferably 1 to 8, and even more preferably 1 to 4). Specifically, examples include butyl (meth)acrylate, 2-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, tridecyl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and benzyl (meth)acrylate. Furthermore, examples of (meth)acrylic acid ester monomers having functional groups such as hydroxyl groups include (meth)acrylic acid ester monomers in which the cycloalkyl group, benzyl group, or alkyl group constituting the ester in the above-mentioned (meth)acrylic acid ester has a hydroxyl group, and hydroxyalkyl (meth)acrylates are preferred, for example, 2-hydroxyethyl (meth)acrylate. Furthermore, examples of (meth)acrylic acid ester monomers having a polyether structure include glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate, with methoxyethylene glycol (meth)acrylate being preferred from the viewpoint of interaction (dispersibility) with antistatic agents. Furthermore, the (meth)acrylic acid ester copolymer may also contain, in addition to the above-mentioned constituent units, constituent units derived from carboxyl group-containing monomers such as crotonic acid, maleic acid, itaconic acid, fumaric acid, acrylamide N-glycolic acid, and cinnamic acid, as well as constituent units derived from copolymerizable monomers such as vinyl acetate, styrene, and acrylonitrile. Examples of acrylic copolymers containing the above-mentioned polyether structure include the DISPERBYK series 2000 and 2001 (both trade names, manufactured by BYK).
[0029] Polyurethane resin is a polymer having urethane bonds within its molecule, and is obtained by reacting a polyether polyol and / or polyester polyol having hydroxyl groups with a polyisocyanate compound. Examples of the above polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, and polytetramethylene ether glycol. Examples of the above polyester polyols include polycarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, sebacic acid, fumaric acid, maleic acid, and terephthalic acid, or their acid anhydrides, and ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2-methyl-2,4-pentanediol. Examples of reaction products with polyhydric alcohols such as tandiol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, and lactonediols. Examples of the above polyisocyanate compounds include aromatic ring-containing diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylenediphenyl diisocyanate, and phenylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, and isophorone diisocyanate. Furthermore, polyurethane may have basic adsorption groups, such as tertiary amino groups, in its molecule. Furthermore, polyurethanes containing a polyether structure or a polyester structure in the side chains are preferred. Examples of such polyurethanes include BYK-9076 and the DISPERBYK series 182, 161, 162, 163, 2163, and 2164 (all are product names, manufactured by BYK).
[0030] The thickness of the antistatic coating layer 10 is not particularly limited as long as the surface resistivity R1 and the surface resistivity change rate Z satisfy (1) and (2) above. For example, the thickness of the antistatic coating layer 10 is preferably 10 to 90 nm, more preferably 15 to 85 nm, and even more preferably 20 to 80 nm. If the tape of the present invention has an antistatic coating layer 10b, it is preferable that the thickness of this antistatic coating layer 10b is also within the above range. If the thickness of the antistatic coating layer 10 is 90 nm or less, it is less likely to affect the physical properties of the base film, and the transparency is less likely to deteriorate even if the antistatic agent is colored. Furthermore, if the thickness of the antistatic coating layer 10 is 10 nm or more, coating unevenness is less likely to occur, and variations in antistatic performance are less likely to occur.
[0031] In the antistatic coating layer 10, the carbon nanotube content in the antistatic coating layer 10 can be, for example, 10 to 90% by mass, preferably 15 to 70% by mass, and more preferably 20 to 50% by mass. In the antistatic coating layer 10, the content of the polymer binder in the antistatic coating layer 10 can be, for example, 10 to 90% by mass, preferably 30 to 85% by mass, and more preferably 50 to 80% by mass.
[0032] Preferably, the antistatic coating layer 10 does not contain any antistatic agents other than carbon nanotubes. Examples of antistatic agents other than carbon nanotubes include conductive polymers, conductive inorganic fine particles, metal particles or fibers, ionic compounds, ionic surfactants, etc., as described in Japanese Patent Publication No. 2023-133232. The above-mentioned literature lists polyaniline, polypyrrole, polythiophene, polyquinoxaline, polyethyleneimine, allylamine polymers, etc., as conductive polymers. Polythiophene is a conductive polymer having a 3,4-ethylenedioxythiophene skeleton, for example, poly(3,4-ethylenedioxythiophene) (PEDOT). PEDOT can be used to form a film by using a composite of PEDOT and polystyrene sulfonic acid (PSS) (for example, available from Nagase ChemteX Corporation under the trade name: Denatron Type-P), but there are concerns about corrosion if PSS leaches out due to its high acidity. The proportion of carbon nanotubes in the antistatic agent contained in the antistatic coating layer 10 is preferably 95% by mass or more, and more preferably 98% by mass or more. It is preferable that all of the antistatic agent contained in the antistatic coating layer 10 is carbon nanotubes.
[0033] Furthermore, the antistatic coating layer 10 may contain additives such as dispersants, colorants, antioxidants, plasticizers, and curing agents, in addition to the components mentioned in the above description of the antistatic agent and binder polymer, as needed, within a range that achieves the effects of the present invention.
[0034] The antistatic coating layer 10 and the antistatic coating layer 10b may have the same or different constituent materials such as the antistatic agent and binder polymer, the content of the constituent materials, and the thickness of the layers.
[0035] (3) Adhesive layer 30 The adhesive layer 30 used in the tape 200 of the present invention may be any layer containing an adhesive, and for example, it may be formed using an adhesive composition. The adhesive layer 30 is used in contact with the uneven surface of the wafer when the tape 200 of the present invention is bonded to the wafer.
[0036] The adhesive constituting the adhesive layer 30 may be a radiation-curing adhesive that hardens upon irradiation, or a radiation-non-curing adhesive that does not harden upon irradiation.
[0037] The adhesive base polymer is not particularly limited, but is preferably a (meth)acrylic polymer. A (meth)acrylic polymer means a copolymer having (meth)acrylic acid ester as a constituent unit. Examples of (meth)acrylic polymers include (meth)acrylic acid ester copolymers consisting of constituent units derived from (meth)acrylic acid ester monomers, or constituent units derived from (meth)acrylic acid monomers and constituent units derived from (meth)acrylic acid. Here, as the (meth)acrylic acid ester monomer, for example, the (meth)acrylic acid ester monomer used in the antistatic coating layer 10 described above, or a (meth)acrylic acid ester monomer having a functional group such as a hydroxyl group can be used.
[0038] The mass-average molecular weight of the adhesive-based polymer is preferably around 200,000 to 1,500,000, and more preferably 700,000 to 1,200,000, from the viewpoint of suppressing contamination of the wafer surface and suppressing gelation during synthesis and coating.
[0039] If the adhesive layer 30 is radiation-curable, in order to make the adhesive layer 30 radiation-polymerizable, the adhesive layer 30 may contain, in addition to the (meth)acrylic polymer, a compound having radiation-polymerizable ethylenically unsaturated groups (radiation-curable unsaturated carbon-carbon double bonds) (preferably a polymerizable compound with a molecular weight of 500 to 20000). It is also preferable to introduce ethylenically unsaturated groups into the (meth)acrylic polymer itself (a base polymer having ethylenically unsaturated groups is referred to as a "(meth)acrylic polymer having ethylenically unsaturated groups"). Alternatively, ethylenically unsaturated groups may be introduced into the (meth)acrylic polymer itself, and a compound having ethylenically unsaturated groups may be included in the coexistence. Furthermore, the adhesive preferably contains a crosslinking agent. Furthermore, if the adhesive is radiation-curable, it is preferable to include a photopolymerization initiator.
[0040] - (meth)acrylic polymer having ethylenically unsaturated groups The iodine value, which is an indicator of the amount of double bonds contained in the polymer, is preferably 0.5 to 30, and more preferably 0.8 to 30, from the viewpoint of obtaining an effect of reducing adhesiveness due to radiation irradiation and preventing excessive radiation hardening. Furthermore, (meth)acrylic polymers having ethylenically unsaturated groups preferably have a glass transition temperature (Tg) of -70°C to 0°C, from the viewpoint of heat resistance to the heat generated during the wafer processing process. The acid value of the (meth)acrylic polymer having ethylenically unsaturated groups [the number of mg of potassium hydroxide required to neutralize the free fatty acids present in 1 g of polymer] is preferably 0.5 to 30 mg KOH / g, and more preferably 1 to 20 mg KOH / g. The hydroxyl value of (meth)acrylic polymers having ethylenically unsaturated groups [the number of mg of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of polymer is acetylated] is preferably 5 to 100 mg KOH / g, and more preferably 10 to 80 mg KOH / g.
[0041] The (meth)acrylic polymer having an ethylenically unsaturated group may be produced by any means, but a preferred method is to introduce an ethylenically unsaturated group into the side chain of the (meth)acrylic polymer by reacting a compound having an ethylenically unsaturated group and a functional group (β) that reacts with the functional group (α) in the polymer with a (meth)acrylic polymer having a functional group (α) in its side chain. The functional group (α) and the functional group (β) may each be one type or two or more types.
[0042] There are no particular limitations on the ethylenically unsaturated group, but (meth)acryloyl group, (meth)acryloyloxy group, (meth)acryloylamino group, allyl group, 1-propenyl group, and vinyl group are preferred, with (meth)acryloyl group or (meth)acryloyloxy group being more preferred. Examples of functional group (β) that react with functional group (α) include carboxyl group, hydroxyl group, amino group, sulfanyl group, cyclic acid anhydride group, epoxy group, and isocyanate group.
[0043] Here, if one of the functional groups (α) and (β) is a carboxyl group, hydroxyl group, amino group, sulfanyl group, or cyclic acid anhydride group, the other functional group may be an epoxy group or an isocyanate group. If one of the functional groups is a cyclic acid anhydride group, the other functional group may be a carboxyl group, hydroxyl group, amino group, or sulfanyl group. If one of the functional groups is an epoxy group, the other functional group may also be an epoxy group.
[0044] (Meth)acrylic polymers having a functional group (α) in the side chain are obtained by polymerizing at least one of (meth)acrylic acid esters, (meth)acrylic acid, and (meth)acrylamide having a functional group (α). Examples of functional group (α) include carboxyl groups, hydroxyl groups, amino groups, sulfanyl groups, cyclic acid anhydride groups, epoxy groups, and isocyanate groups, and it is preferable that at least one of a carboxyl group and a hydroxyl group be included, and more preferably that at least one of a hydroxyl group be included.
[0045] Examples of monomers having a functional group (α) include (meth)acrylic acid, methacrylic acid, cinnamic acid, itaconic acid, fumaric acid, phthalic acid, 2-hydroxyalkyl (meth)acrylate, glycol mono(meth)acrylate, N-methylol(meth)acrylamide, allyl alcohol, N-alkylaminoethyl (meth)acrylate, (meth)acrylamide, maleic anhydride, itaconic anhydride, fumaric anhydride, phthalic anhydride, glycidyl (meth)acrylate, and allyl glycidyl ether, and polyisocyanate compounds in which a portion of the isocyanate group is urethaned with monomers having a hydroxyl group or carboxyl group and a radiation-curable carbon-carbon double bond. Among these, (meth)acrylic acid, 2-hydroxyalkyl (meth)acrylate, or glycidyl (meth)acrylate is preferred, (meth)acrylic acid or 2-hydroxyalkyl (meth)acrylate is more preferred, and 2-hydroxyalkyl (meth)acrylate is even more preferred. The monomer having the functional group (α) may be one type or two or more types.
[0046] The (meth)acrylic polymer having an ethylenically unsaturated group is preferably a copolymer with a monomer other than the monomer having the above-mentioned functional group (α) (for example, other monomers such as (meth)acrylic acid esters that do not have the above-mentioned functional group (α)). Examples of (meth)acrylic acid esters that do not have the above-mentioned functional group (α) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate methacrylate. The (meth)acrylic acid ester that does not have the above-mentioned functional group (α) may be used individually or in combination of two or more types.
[0047] The polymerization reaction of (meth)acrylic polymers having ethylenically unsaturated groups may be carried out by solution polymerization, emulsion polymerization, bulk polymerization, or suspension polymerization. When a (meth)acrylic polymer having a functional group (α) in its side chain is synthesized by reacting it with a compound having an ethylenically unsaturated group and a functional group (β) that reacts with the functional group (α) in the polymer, a polymer with a desired acid value and hydroxyl value can be prepared by leaving unreacted functional groups.
[0048] There are no particular restrictions on the polymerization initiator used in the polymerization of (meth)acrylic polymers having ethylenically unsaturated groups. For example, radical generators such as azobis-based agents like α,α'-azobisisobutylnitrile and organic peroxide-based agents like benzoyl peroxide are commonly used. In this case, catalysts and polymerization inhibitors can be used in combination as needed, and polymers with desired molecular weights can be obtained by adjusting the polymerization temperature and polymerization time. Furthermore, it is preferable to use mercaptan or carbon tetrachloride-based solvents to adjust the molecular weight.
[0049] This section describes compounds having an ethylenically unsaturated group and a functional group (β). The ethylenically unsaturated group and functional group (β) are as described above. The isocyanate group is particularly preferred as the functional group (β).
[0050] Examples of compounds having an ethylenically unsaturated group and a functional group (β) include (meth)acrylic acid esters having an isocyanate group in the alcohol portion. For (meth)acrylic acid esters having an isocyanate group in the alcohol portion, those having an isocyanate group at the end of the alcohol portion are preferred, the number of carbon atoms other than the isocyanate group in the alcohol portion is preferably 2 to 8, and the alcohol portion is preferably a linear alkyl group. For example, 2-isocyanatoethyl (meth)acrylate is a preferred example of a (meth)acrylate having an isocyanate group in the alcohol portion.
[0051] As an adhesive in which an ethylenically unsaturated group is introduced into the adhesive base polymer itself and a compound having an ethylenically unsaturated group is present, for example, the description relating to an adhesive containing a radiation-polymerizable low molecular weight compound described in
[0059] to
[0064] of International Publication No. 2018 / 181240 can be applied.
[0052] -Crosslinking agent- The adhesive layer 30 described above preferably has a certain degree of cross-linking structure in the (meth)acrylic polymer (before the photocuring reaction if the adhesive is radiation-curable). Preferred cross-linking agents for forming the cross-linking structure include polyisocyanates, melamine-formaldehyde resins, and epoxy resins, with polyisocyanates being particularly preferred. The cross-linking agent may be used alone or in combination of two or more types. By incorporating a cross-linking agent, the cohesive force of the adhesive can be improved after application.
[0053] There are no particular restrictions on the polyisocyanates, and examples include aromatic isocyanates such as 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4'-[2,2-bis(4-phenoxyphenyl)propane] diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethyl-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, lysine diisocyanate, lysine triisocyanate, and adducts of these isocyanate compounds with polyol compounds such as trimethylolpropane; burettes and isocyanurates of these isocyanate compounds; and so on.
[0054] Specifically, melamine-formaldehyde resins such as Nikalac MX-45 (product name, manufactured by Sanwa Chemical Co., Ltd.) and Melan (product name, manufactured by Hitachi Chemical Co., Ltd.) can be used. As the epoxy resin, TETRAD-X (trade name, manufactured by Mitsubishi Chemical Corporation) can be used.
[0055] The amount of crosslinking agent added is preferably 0.1 to 20 parts by mass, and more preferably 1.0 to 10 parts by mass, per 100 parts by mass of the adhesive base polymer, from the viewpoint of exhibiting an effect of improving cohesive force, suppressing the formation of crosslinked structures due to the rapid progress of the curing reaction, and not impairing workability. The amount can be appropriately adjusted according to the number of functional groups of the (meth)acrylic polymer having ethylenically unsaturated groups, and in order to obtain the desired adhesive properties and elastic modulus.
[0056] -Photopolymerization initiator- The photopolymerization initiator is not particularly limited as long as it reacts to radiation transmitted through the antistatic coated substrate film 100, and commonly used ones can be used. Examples include benzophenones such as benzophenone, 4,4'-dimethylaminobenzophenone, 4,4'-diethylaminobenzophenone, and 4,4'-dichlorobenzophenone; acetophenones such as acetophenone and diethoxyacetophenone; α-hydroxyketones such as oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone] and 2-hydroxy-2-methyl-1-phenyl-1-propanone; anthraquinones such as 2-ethylanthraquinone and t-butylanthraquinone; 2-chlorothioxanthone, benzoin ethyl ether, benzoin isopropyl ether, benzyl, 2,4,5-trially-ruimidazole dimer (rophine dimer), acridine compounds, acylphosphine oxides, etc. These may be used individually, or in combination of two or more types. The amount of photopolymerization initiator added is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 7 parts by mass, per 100 parts by mass of (meth)acrylic polymer having ethylenically unsaturated groups.
[0057] -Other additives- The adhesive layer 30 may contain tackifiers, tackiness modifiers, surfactants, or other modifiers as needed. In addition, inorganic compound fillers may be added as appropriate. In the present invention, the addition of modifiers is also preferable from the viewpoint of release properties. Furthermore, the description relating to radiation-curable additives described in paragraph
[0050] of Japanese Patent Publication No. 2022-109374 can be preferably applied.
[0058] The thickness of the adhesive layer 30 is preferably 20 to 80 μm, more preferably 25 to 75 μm, and even more preferably 30 to 70 μm.
[0059] In the tape 200 of the present invention, both the adhesive layer 30 and the base film 20 preferably do not contain an antistatic agent, and preferably contain 1% by mass or less. Examples of such antistatic agents include materials commonly used for antistatic purposes. For example, conductive polymers, conductive inorganic fine particles, metal particles or fibers, ionic compounds, ionic surfactants, etc., as described in Japanese Patent Application Publication No. 2023-133232. Even in such an embodiment (where the adhesive layer 30 and / or base film 20 do not contain an antistatic agent), the tape 200 of the present invention can exhibit desired antistatic properties and water resistance.
[0060] (4) Method for manufacturing the tape 200 of the present invention The method for manufacturing the tape 200 of the present invention is not particularly limited and can be manufactured by conventional methods. The tape 200 of the present invention can be manufactured, for example, by forming an antistatic coating layer 10 on one side of a base film 20 to form an antistatic coated base film 100, and further forming an adhesive layer 30 on the side of the antistatic coated base film 100 opposite to the antistatic coating layer 10 (the base film 20 side).
[0061] The method for manufacturing the antistatic coating layer substrate film 100 is not particularly limited. Examples include a method of directly applying a composition for forming the antistatic coating layer 10 (antistatic coating layer composition) onto the substrate film 20 using a coater such as a gravure coater, bar coater, knife coater, or roll coater, and a method of printing the antistatic coating layer composition as ink onto the substrate film 20 by relief printing, recessed printing, planar printing, flexographic printing, offset printing, or screen printing. Among these, the method of directly applying the antistatic coating layer composition onto the substrate film 20 using a gravure coater (gravure coating) is preferred from the viewpoint of being able to form a thin film antistatic coating layer 10. The dispersion medium in the film obtained by the above-mentioned coating and printing methods is removed by drying or the like to form the antistatic coating layer 10. If the tape 200 of the present invention has an antistatic coating layer 10b, the antistatic coating layer 10 and the antistatic coating layer 10b may be formed simultaneously on the base film 20, or one antistatic coating layer may be formed first, and then the remaining antistatic coating layer may be formed. The composition for the antistatic coating layer is typically a dispersion in which carbon nanotubes and a binder polymer are dispersed. The dispersion medium is not particularly limited and, depending on the type of antistatic agent and binder polymer, may include, for example, water, alcohols such as ethanol, polar organic solvents such as lactam solvents such as N-methylpyrrolidone, nonpolar organic solvents, and combinations of these solvents. Water or a mixture of water and an alcohol-based solvent is preferred in terms of handling and working environment. Furthermore, the composition for the antistatic coating layer may further contain the additives listed in the above-described antistatic coating layer 10.
[0062] The adhesive layer 30 can be formed by applying and drying a composition for forming the adhesive layer 30 (adhesive composition) onto the base film 20. Alternatively, the adhesive composition can be applied and dried onto a release film, and the resulting adhesive layer 30 can be laminated as a layer constituting the tape 200 of the present invention by laminating or transferring it onto the base film 20 or a base film 100 with an antistatic coating layer. As the solvent in the adhesive composition, solvents such as ethyl acetate can be used. [Examples]
[0063] The present invention will be described in more detail based on examples, but the present invention is not limited thereto.
[0064] <Preparation of adhesive composition Y1> As an acrylic polymer, a copolymer was prepared consisting of 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, and methacrylic acid, with a ratio of 55 mol% 2-ethylhexyl acrylate and a mass-average molecular weight of 750,000. By adding 2-isocyanatoethyl methacrylate to the obtained copolymer to achieve an iodine value of 25 and reacting the mixture, acrylic polymer A was prepared with a glass transition temperature of -50°C, a hydroxyl value of 10 mg KOH / g, and an acid value of 5 mg KOH / g. To 100 parts by mass of acrylic polymer A, 1 part by mass of trimethylolpropane adduct-type modified tolylene diisocyanate (TDI-TMP adduct) was added as a crosslinking agent, and 5 parts by mass of Esacure KIP100F (trade name) (manufactured by Lamberti, a mixture of oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone] (70%) and 2-hydroxy-2-methyl-1-phenyl-1-propanone (30%)) was added as a photopolymerization initiator. This mixture was dissolved in ethyl acetate and stirred to prepare adhesive composition Y1.
[0065] <Preparation of substrate films with antistatic coating layer> (Preparation of substrate films with antistatic coating for Examples 1-3 and Comparative Examples 4 and 5) (1) Preparation of a substrate film with an antistatic coating layer for Example 1 A 50 μm thick polyethylene terephthalate (PET) film (product name: Lumirror X43, manufactured by Toray Industries, Inc.) was used as the base film. An aqueous dispersion CP1 (composition for antistatic coating layer), a mixture of a carbon nanotube aqueous dispersion (product name: Conductive Coat CNT Y-545, manufactured by Chukyo Oil & Fat Co., Ltd.) as an antistatic agent and an aqueous dispersion of an acrylic resin having a polyether structure (manufactured by Chukyo Oil & Fat Co., Ltd.) (hereinafter referred to as acrylic resin a1) as a binder polymer, was gravure coated onto one side of this base film to produce a base film with an antistatic coating layer for Example 1. The carbon nanotube content in this antistatic coating layer was 30% by mass, and the acrylic resin a1 content was 70% by mass. (2) Preparation of antistatic coated substrate films for Examples 2-3 and Comparative Examples 4 and 5 In preparing the substrate film with an antistatic coating layer for Example 1, the substrate films with antistatic coating layers for Examples 2-3 and Comparative Examples 4 and 5 were prepared in the same manner, except that the thickness of the antistatic coating layer was varied. The thickness of the antistatic coating layer was adjusted by the coating thickness of the aqueous dispersion CP1 before drying and the solid content concentration in the aqueous dispersion CP1.
[0066] (Preparation of substrate films with antistatic coating for Comparative Examples 1-3) A 50 μm thick polyethylene terephthalate film (product name: Lumirror X43, manufactured by Toray Industries, Inc.) was used as the base film. A dispersion of the antistatic agent PEDOT / PSS (a dispersion of a composite material consisting of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid) and an aqueous dispersion of an acrylic resin having a polyether structure as a binder polymer (manufactured by Chukyo Oil & Fat Co., Ltd.) (acrylic resin a1) was gravure coated onto one side of this base film to the thickness shown in Table 1, thereby producing base films with antistatic coating layers for Comparative Examples 1 to 3. The PEDOT / PSS content in this antistatic coating layer (A2) was 30% by mass, and the acrylic resin a1 content was 70% by mass.
[0067] <Preparation of antistatic adhesive tape for backgrinding> (Example 1) A polyethylene terephthalate film (38 μm thick) treated with a silicone release agent was coated with adhesive composition Y1 using a comma coater at a linear speed of 2 m / min, and an adhesive layer was formed by passing it through a hot air drying oven set to 110°C. Subsequently, the adhesive layer was transferred by laminating it with the antistatic coated base film for Example 1, thereby producing the antistatic adhesive tape for backgrinding in Example 1. During the transfer process, the adhesive layer was laminated to the side of the base film opposite to the antistatic coated layer. (Examples 2 and 3, and Comparative Examples 1-5) In the preparation of the antistatic adhesive tape for backgrinding in Example 1 described above, the antistatic coating layer and the base film were modified to have the configuration shown in Table 1 by using the antistatic coating layer base films for Examples 2 and 3 and Comparative Examples 1 to 5, respectively, instead of the antistatic coating layer base film for Example 1. Otherwise, the antistatic adhesive tapes for backgrinding in Examples 2 and 3 and Comparative Examples 1 to 5 were prepared in the same manner as the antistatic adhesive tape for backgrinding in Example 1.
[0068] The antistatic adhesive tapes 200 for backgrind obtained in this manner in Examples 1 to 3 and Comparative Examples 1 to 5 have a structure in which an antistatic coating layer 10, a base film 20, and an adhesive layer 30 are laminated in this order, as shown in Figure 1.
[0069] Table 1 shows the components and thicknesses of the antistatic coating layer 10, base film 20, and adhesive layer 30 of the obtained antistatic adhesive tape for backgrinding (hereinafter also simply referred to as "adhesive tape"). Furthermore, the antistatic adhesive tape obtained for backgrinding was evaluated for its antistatic performance and water resistance. These results are summarized in Table 1.
[0070] <thickness> The thickness was measured on a surface plate using a spindle-type dial gauge (manufactured by Mitutoyo Corporation).
[0071] <Evaluation of antistatic performance> (Surface resistivity) The above adhesive tape was cut to a measurement shape (100mm x 100mm) using the Resistivity Chamber R12702A (manufactured by Advantest). Using a digital ultra-high resistance / micro-current meter 8340A and the Resistivity Chamber R12702A (both manufactured by Advantest), a voltage of 10V was applied for 60 seconds to the antistatic coating layer side (opposite the adhesive layer) under conditions of 23°C and 50% relative humidity. The surface resistivity R1 was measured by reading the current value immediately after the end of the 60-second application period. The above measurement sample was processed under the following conditions (process (A)). The surface resistivity R2 was measured on the sample after this process (A) in the same manner as the surface resistivity R1 described above. In addition, the rate of change of surface resistivity Z was calculated based on the following (equation I). (Equation I) Surface resistivity change rate Z = Surface resistivity R² / Surface resistivity R¹ (Process (A)) A sample of the antistatic adhesive tape for backgrinding (100mm x 100mm) was immersed in pure water at 23°C for 24 hours. Afterwards, the immersed sample was removed, lightly rinsed with pure water, drained, dried at 23°C, and then left to stand for 12 hours in an atmosphere of 23°C and 50% relative humidity. A large increase in the surface resistivity change rate Z indicates that the antistatic performance has decreased as a result of the antistatic agent leaching out or detaching from the antistatic coating layer of the adhesive tape.
[0072] <Water resistance test (B)> The water resistance of each adhesive tape was evaluated using pH as an indicator. Specifically, the tests were conducted as follows: A sample of antistatic adhesive tape for backgrinding (100mm x 100mm) was immersed in 10 ml of pure water at 23°C for 24 hours in a 120 mm x 120 mm plastic container. The pH of the resulting immersion solution was then measured using pH test paper. The pH of the pure water before immersion was 7. For the above measurements, pH test paper (product name: pH Test Paper Roll Type UNIV (1-11) with color change chart, 9mm x 6m, manufactured by Advantec Toyo Co., Ltd.) was used. In the "Properties" column of the water resistance test in Table 1, a pH of 6-9 in the immersion solution after immersion is described as "neutral," and a pH of 5 or lower is described as "acidic."
[0073] [Table 1]
[0074] The unit of surface resistivity is Ω / sq. The "Acrylic Polymer" column in the table lists the adhesive base polymer. "A" is acrylic polymer A contained in the adhesive composition Y1 described above.
[0075] From the results in Table 1, the following can be seen. The adhesive tapes in Comparative Examples 1-3 used PEDOT / PSS instead of carbon nanotubes as an antistatic agent. These adhesive tapes in Comparative Examples 1-3 had a large surface resistivity change rate Z of 139 or higher, indicating poor water resistance. In addition, the pH of the immersion solution after test (B) decreased to 5 or below. In both cases, it is thought that the antistatic agent PEDOT / PSS leached into the water. The adhesive tapes of Comparative Examples 4 and 5 have a surface resistivity R1 of 1.0 × 10 as defined in the present invention. 5 ~1.0×10 12The adhesive tape has a surface resistivity that is either too high or too low relative to Ω / sq. In Comparative Example 4, the surface resistivity R1 of the adhesive tape is too high, and it cannot be said to have sufficient antistatic properties for production due to errors such as sticking caused by static electricity during transport of the adhesive tape. In Comparative Example 5, the surface resistivity R1 and R2 of the adhesive tape are too low, so electricity flows too easily in processes such as using an antistatic chuck for wafer fixing or using a laser, causing problems in the wafer processing process. In contrast, the antistatic adhesive tapes for backgrinding described in Examples 1 to 3 of the present invention satisfy the surface resistivity R1 and surface resistivity change rate Z specified in the present invention, and the pH after test (B) was 7, resulting in excellent antistatic properties and water resistance. It is believed that these adhesive tapes, because the antistatic agent is carbon nanotubes, do not easily leach from the antistatic coating layer, thus maintaining their antistatic performance even after test (B), and resulting in excellent water resistance. [Explanation of symbols]
[0076] 10. Antistatic coating layer 20 Base film 30 Adhesive layer 100 Antistatic coated substrate film 200 Antistatic Adhesive Tape for Backgrinding
Claims
1. An antistatic adhesive tape for backgrinding comprising an antistatic coating layer, a base film, and an adhesive layer in this order, The antistatic coating layer contains carbon nanotubes as an antistatic agent, If, before the following treatment (A), the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R1, and after the following treatment (A), the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R2, Antistatic adhesive tape for backgrinding that satisfies the following conditions (1) and (2). (1) The surface resistivity R1 is 1.0 × 10 5 ~1.0 x 10 12 It is Ω / sq. (2) The surface resistivity change rate Z calculated by the following formula (Equation I) is between 1.0 and 20.
0. (Equation I) Surface resistivity change rate Z = Surface resistivity R² / Surface resistivity R¹ <Process (A)> A sample of the antistatic adhesive tape for backgrinding (100 mm x 100 mm) is immersed in pure water at 23°C for 24 hours, then removed, lightly rinsed with pure water, drained, dried at 23°C, and left to stand for 12 hours in an atmosphere of 23°C and 50% relative humidity.
2. The antistatic adhesive tape for backgrinding according to claim 1, wherein the pH measured by the following water resistance test (B) is in the range of 6 to 8. <Water resistance test (B)> A sample of the antistatic adhesive tape for backgrinding (100 mm x 100 mm) is immersed in 10 ml of pure water at 23°C for 24 hours, and the pH of the resulting immersion solution is measured using pH test paper.
3. The antistatic adhesive tape for backgrinding according to claim 1, wherein the thickness of the antistatic coating layer is 10 to 90 nm.
4. The antistatic adhesive tape for backgrinding according to claim 1, wherein the base film contains polyester resin.
Citation Information
Patent Citations
Pressure sensitive adhesive sheet
JP2023133232A
Adhesive sheet for fixing electronic member
WO2021117398A1